Kerugian Keuangan Negara Dalam Tindak Pidana Korupsi Tabungan Wajib Perumahan TNI AD (Analisis Putusan Kasasi No: 407K/Mil/2023 Tanggal 7 Desember 2023) - Kantor Kantor; Sujono Sujono (Neolectura, 2026)
The determination of state financial loss constitutes a fundamental element in proving corruption offenses. Legal complexities arise when the managed funds do not originate directly from the State Budget, such as the Mandatory Housing Savings Fund (Tabungan Wajib Perumahan/TWP) of the Indonesian National Armed Forces (Army). Although the TWP fund is collected through mandatory salary deductions from military personnel for welfare purposes, its management is conducted within the structure of a state institution, giving rise to legal debates regarding its status. This article aims to provide a juridical analysis of the qualification of the TWP Army fund as state finances and its implications for proving corruption offenses, based on the Supreme Court Decision of the Republic of Indonesia Number 407K/MIL/2023 dated 7 December 2023. This study employs a normative legal research method using statutory and case approaches. The findings indicate that the TWP Army fund can be normatively classified as part of state finances due to its control, management, and accountability by a state institution. The Supreme Court, through the decision, affirmed that the misuse of the TWP fund resulted in state financial loss, thereby fulfilling an essential element of corruption offenses. This decision provides legal certainty in interpreting the concept of state finances and strengthens accountability as well as the enforcement of anti-corruption law within the military environment.